1997
DOI: 10.1002/eji.1830270820
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐12 acts as an adjuvant for humoral immunity through interferon‐γ‐dependent and ‐independent mechanisms

Abstract: Interleukin-12 (IL-12) is a pivotal cytokine that has dramatic effects on cell-mediated immunity. It is now becoming increasingly recognized that IL-12 also strongly controls humoral immunity. We have investigated the mechanism by which IL-12 induces alterations in antibody isotype expression by determining the influence of IL-12 on in vitro immunoglobulin (Ig) production in polyclonally activated murine spleen cell cultures. Cells exposed to IL-12 plus lipopolysaccharide or anti-CD40 monoclonal antibody showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
5

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 22 publications
3
53
0
5
Order By: Relevance
“…We (15)(16)(17) and others (18 -22) have demonstrated the effectiveness of IL-12 as an adjuvant for humoral immunity in adult animals. In addition, we have found that neonatal animals have reduced IL-12 expression in the periphery and that IL-12 delivered at birth can serve as an adjuvant to induce a Th1-like cytokine response and cause priming for enhanced Ab responses to DNP-OVA and hen eggwhite lysozyme (HEL) 3 (23).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…We (15)(16)(17) and others (18 -22) have demonstrated the effectiveness of IL-12 as an adjuvant for humoral immunity in adult animals. In addition, we have found that neonatal animals have reduced IL-12 expression in the periphery and that IL-12 delivered at birth can serve as an adjuvant to induce a Th1-like cytokine response and cause priming for enhanced Ab responses to DNP-OVA and hen eggwhite lysozyme (HEL) 3 (23).…”
mentioning
confidence: 75%
“…IL-12 is a pivotal cytokine that regulates the biological functions of T cells and NK cells and enhances the production of IFN-␥ and other cytokines (13,14). In addition, IFN-␥ stimulates production of opsonizing Abs such as IgG2a (15,17,31). In the present study, we found that coadministration of IL-12 and influenza vaccine at birth resulted in significant increases in neonatal IFN-␥ mRNA levels.…”
Section: Figurementioning
confidence: 99%
“…The cumulative data from both CD4 ϩ and CD8 ϩ T cells are shown in Fig. 10M to N [42,43], thrombocytes [9], mast cells [75], basophils [60], neutrophils [44], eosinophils [40], macrophages [58], and dendritic cells [33]) as well as lymphoid progenitors (NK-cells ( [25], NK T cells [73], B cells [39], ␥␦-T cells [71], CD4…”
Section: Rag1-dependent Lineages (Ie T and B Cells) Specificallymentioning
confidence: 99%
“…It has been found that the inclusion of IL-12 during intranasal vaccination induces significant levels of both pulmonary IgG and IgA antibodies that are not expressed after exposure to vaccine alone. These increases are partially IFN-g dependent and IFN-g independent [28,29]. In experiments with influenza virus infection, it was found that all mice given only phosphate buffered saline before viral challenge succumbed to influenza, and that intranasal immunization with influenza subunit vaccine alone provided only partial protection.…”
Section: For Reprint Orders Please Contact Reprints@expert-reviewscommentioning
confidence: 99%